Household Food Insecurity and Dietary Saturated Fat in Rural Appalachia - Frances Hardin-Fanning; Debra K. Moser; Mary Kay Rayens (Rural Nurse Organization; Binghamton University, 2019)
Purpose: To explore the relationship between food insecurity and dietary saturated fat intake in rural Central Appalachia. Design: Cross-sectional analysis of baseline data from a longitudinal interventional study Sample: Baseline assessment of dietary saturated fat intake and food security in volunteers who had resided in rural Central Appalachia for at least five years and were enrolled in a cooking skills class. Method: Volunteers (n=56, 89.3% female) completed the USDA Household Food Security Survey Module (HFSSM) and Diet History Questionnaire-II. Average age was 56.5 (range 18-76) years. Average intake of saturated fat was calculated using DietCalc software. Food security was measured using the HFSSM. Descriptive and inferential statistical analyses were conducted using SAS, v. 9.3 with an alpha level of .05. Findings: High or marginal food security was experienced by 75% with 25% of participants experiencing low/very low food security. Average daily saturated fat was 26 grams. Significant findings included greater saturated fat consumption in men; lower saturated fat consumption with older age; older age being associated with lower food insecurity; and no association between food insecurity and saturated fat intake. Average daily saturated fat gram intake was significantly lower for females than males; the group means were 23.6 (SD = 12.4) and 49.6 (SD = 15.0) for these two groups, respectively (t = 4.8, P < .001). For every 10-year increase in age, there was a 2.7 gram decrease in daily saturated fat intake. Conclusions: Historical food traditions and method of food preparation likely contribute to the lack of an association between high food security and saturated fat intake in rural Appalachia. Food insecurity was not associated with saturated fat intake in our sample. Additional research is needed to determine to the full impact of food insecurity on dietary fat intake in Appalachia. Keywords: Food Insecurity, Appalachian Region, Fatty Acids Saturated, Poverty DOI: http://dx.doi.org/10.14574/ojrnhc.v19i1.568 Acknowledgments: This study was funded by the National Institute of Nursing Research Grant 5K23NR014883-02.